A double‐mode cell to measure pitting and crevice corrosion. Issue 12 (11th July 2019) - Shen, Jing; Song, Guang‐Ling; Zheng, Dajiang; Wang, Ziming
Abstract: Pitting corrosion and crevice corrosion of passivated steels were measured by using a double‐mode syringe electrolyte cell built on an environment chamber. The setup, when set in noncontact mode, could measure pitting potentials and critical temperatures, and crevice corrosion potentials if in contact mode. It could be employed to distinguish the pitting and crevice corrosion damage of reinforcing steel in concrete. Abstract : Pitting corrosion and crevice corrosion of passivated steels were measured by using a double‐mode syringe electrolyte cell built on an environment chamber. The setup, when set in noncontact mode, could measure pitting potentials and critical temperatures, and crevice corrosion potentials if in contact mode. It could be employed to distinguish the pitting and crevice corrosion damage of reinforcing steel in concrete.